Ensuring Communicative-Pragmatic Adequacy in the Translated Text - Abdullayeva, Shoxida Norqulovna (The Lingua Spectrum, 2026)
The article examines theoretical and applied conditions for ensuring communicative-pragmatic adequacy in translation. Adequacy is treated not as formal correspondence between linguistic units, but as the degree to which the target text reconstructs the source text’s communicative purpose, authorial intention, illocutionary force, implicature, evaluative tone, register, and functional effect on the addressee. Using comparative-pragmatic, contextual, and functional analysis, the study discusses recurrent situations in which lexical equivalence alone is insufficient, including politeness, irony, implicit evaluation, cultural presupposition, headlines, and directive utterances. A six-component model is proposed for assessing communicative-pragmatic adequacy: semantic accuracy, preservation of intention, illocutionary force, recipient orientation, discourse-register correspondence, and cultural accessibility. The paper also outlines a four-stage decision procedure for translators: identifying the communicative situation, determining the pragmatic core and risk zones, selecting an appropriate transformation, and testing the probable effect of the target text. The model is applicable to literary, journalistic, popular-science, and institutional translation practice.